The Emerging Role of Circular RNAs in Alzheimer’s Disease and Parkinson’s Disease - Zhang, Meng; Bian, Zhigang (Frontiers in Aging Neuroscience, 2021)
Alzheimer’s disease (AD) and Parkinson’s disease (PD) are two neurodegenerative diseases (NDDs) commonly found in elderly patients that are difficult to diagnose and lack effective treatment. Currently, the available diagnostic methods for these two NDDs do not meet clinical diagnostic expectations. Circular RNAs (circRNAs) are a diverse group of endogenous non-coding RNAs (ncRNAs) found in eukaryotic cells. Emerging studies suggest that altered expression of circRNAs is involved in the pathological processes of NDDs. CircRNAs could also prove to be promising biomarkers for the early diagnosis of NDDs such as AD and PD. Growing evidence has improved our knowledge of the roles of circRNAs in NDDs, which may lead to new therapeutic approaches that target transcription for preventing neurodegeneration. In this review, we describe the formation mechanisms and functions of circRNAs as well as methods of validation. We also discuss the emerging role of circRNAs in the pathophysiology of AD and PD and their potential value as biomarkers and therapeutic targets for AD and PD in the future.